The American Boycott of British Goods, 1764–1770: A Marcusean Critique of the Marketplace of Revolution - Korolija, Aleksandar Z. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
This paper critically examines the American boycott of British goods between 1764 and 1770 through the lens of Herbert Marcuse’s theory of false needs and consumer society, in dialogue with Timothy Breen’s notion of the marketplace of revolution. While Breen emphasizes the transformative role of consumer resistance in forging colonial political identity, this article questions the depth and sincerity of anti-consumerist sentiment during the boycott. It argues that the boycott was primarily a tactical reaction to British coercion, rather than a strategic rejection of consumerism. Drawing on secondary sources and historiography, the analysis reveals sharp class contradictions in the organization, enforcement, and symbolic meaning of boycotts across regions and social groups. The article contends that neither Breen nor Marcuse adequately integrate class struggle into their interpretations. By incorporating class analysis, it highlights the different motives of merchants, artisans, planters, and lower classes, showing that the boycott often reproduced existing inequalities. The study concludes that the ephemeral nature of anti-consumerist discourse and the rapid return to consumption following British concessions suggest that marketplace resistance was limited in ideological and political depth and largely failed to really challenge the underlying capitalist logic.
Keywords: Herbert Marcuse; Timothy Breen; boycott; American colonies; consumerism; class struggle; false needs; anti-consumerist discourse; marketplace of revolution; political identity